Better rich, or better there?: grandparent wealth, coresidence, and intrahousehold allocation - Quisumbing, Agnes R. (International Food Policy Research Institute, 1997)
This paper uses three-generation retrospective data from the rural Philippines to examine the role of the extended family, proxied by alternative measures of grandparent coresidence, on investments in children. An extension of the wealth model of intergenerational transfers shows that extended family resources may affect transfers to children if parents are credit constrained. Family-level unobservables are important in determining the allocation of education and land between sons and daughters. Both parent and grandparent pre-marriage wealth affect children’s completed schooling levels. Grandparent wealth, however, does not seem to affect the distribution of education between sons and daughters, although it affects the allocation of land. Grandparent influence on child schooling appears to work through proximity rather than through wealth. Sons are clearly favored in terms of land inheritance, while daughters get more education. Better educated fathers favor daughters in terms of education, while mothers with more land favor sons. These patterns are consistent with both equity and efficiency objectives, investment in children under resource constraints, and parents' risk-diversification strategies.